Upaya meningkatkan kinerja pemasaran pada era digital - Amin Mansur; Any Setianingrum; Muslikh Muslikh (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2017)
Purpose: The objective of this study is find out how the attempt to increase market performance of micro and small medium enterprises in Bekasi City. In addition, this study olso examines the effect of market orientation, product innovation, and competitiveness on market performance in the digital era. Methodology: This research was conducted by survey by distributing questionnaires to 114 micro and small medium enterprise actors. The samplingof research used non probability sampling with purposive sampling technique. Findings: The results indicate that market orientation and innovation influence significantly competitiveness, market orientation influences market performance, product innovation influences market performance, and competitiveness influences market performance of small and medium enterprises in Bekasi City. Keywords: market orientation, innovation, competitiveness, market performance , digital era, SMEs.